Cover Feature: Multi‐faceted Set‐up of a Diverse Ketoreductase Library Enables the Synthesis of Pharmaceutically‐relevant Secondary Alcohols (6/2021). Issue 6 (25th February 2021) - Voss, Moritz; Küng, Robin; Hayashi, Takahiro; Jonczyk, Magdalena; Niklaus, Michael; Iding, Hans; Wetzl, Dennis; Buller, Rebecca
Abstract : The Cover Feature highlights the synthetic potential of a diverse, off‐the‐shelf ketoreductase library for the selective reduction of small molecule ketones. In their Full Paper, M. Voss, R. Küng et al. present the multi‐faceted set‐up of a diverse ketoreductase library and demonstrate the use of 51 enzymes for the synthesis of valuable building blocks. Linking function with the respective protein sequences enabled the assignment of amino acid patterns to the observed enantioselectivities. The availability of this ready‐to‐screen enzyme library, including 29 novel ketoreductases, is expected to accelerate the implementation of biocatalytic steps in industrial processes and to guide further enzyme sourcing campaigns. (Created with BioRender.com).More information can be found in the Full Paper by M. Voss, R. Küng et al .